KAJIAN ATRIBUT PADA AKTIVITAS PEDAGANG PASAR INFORMAL DI PASAR LOAK JEMBATAN ITEM, JAKARTA - Dedi Hantono; Wiendu Nuryanti; Diananta Pramitasari (Universitas Muhammadiyah Jakarta, 2024)
Urban public open spaces have very high accessibility, making it easier for various activities to emerge even though they are not by the function of the area, including trading activities. Trading activities that grow in public open spaces lead to the growth of informal market spaces that often get pressure from the environment. The efforts of informal market traders to survive are studied through the attributes contained in the market space. A qualitative research method with a case study approach is needed to answer the